PENGARUH KEGIATAN SAFETY AWARENESS TERHADAP KAWASAN KESELAMATAN OPERASIONAL PENERBANGAN BANDARA INTERNASIONAL SAM RATULANGI MANADO - Muhammad Ryamizard Ramadhani; Ariyono Setiawan; Yuyun Suprapto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
With the increasing number of requests for air transport services, the traffic and activities that occur in the airspace and airport areas will also increase. People who live in the area around the airport, of course, cannot evade the regulations on the flight operational safety area. For this reason, airports need to pay attention to this, because the existence of an airport is expected to be able to provide positive synergy to all aspects to minimize the things we don't want. This study aims to ascertain whether the efforts made have fully met the standards in maintaining the operational safety area of ​​flights with the existence of flight activities at Sam Ratulangi Airport in Manado in accordance with the Decree of the Minister of Transportation No. KM 11 of 2010 concerning the National Airport Order. This quantitative descriptive research method refers to the Decree of the Minister of Transportation No. KM 11/2010 concerning the National Airport Order and the Airport Services Manual (ICAO) doc. 9137 Part 6. Control Of Obstacle. Methods of data collection using the method of observation, questionnaires and literature study. The result of this research is a lack of public awareness of 10.7%. In addition, increasing public awareness of the flight operation safety area by 89.3%.